Immune Checkpoint Inhibitors and the Heart - Mocan-Hognogi, Diana Larisa; Trancǎ, Sebastian; Farcaş, Anca Daniela; Mocan-Hognogi, Radu Florin; Pârvu, Andrada Viorica; Bojan, Anca Simona (Frontiers in Cardiovascular Medicine, 2021)
Immune checkpoint inhibitors (ICIs) represent break-through treatment for a various number of cancers and their indication is continuously expanding. They are prescribed for primary tumors and for metastases, adjuvant and neoadjuvant therapy so there is an increased need for expertise in different aspects of the ICIs including the ways of response and toxicities related to them ICIs become toxic because of the removal of self-tolerance, which in turn promotes autoimmune processes that affect every organ, but when related to the heart, it has been noticed to be leading to acute heart failure and even death through various mechanisms (myocarditis, pericarditis, arrhythmia and Takotsubo cardiomyopathy) This review aims to address the above concerns by focusing on the latest findings on the topic, some insight on the mechanism of action of ICIs with special consideration regarding the myocardial tissue and providing information on clinical manifestation, diagnosis and (wherever possible) treatment of the cardiotoxic events related to this therapy. . The information is scarce and in most cases, the articles we found refer mainly to case-presentations and studies that were conducted on small populations, but we consider that it is worthwhile to be aware of it, , especially since this treatment is now widely used and it provides an important increase of the survival rate in patients who receive it.